Configuration analysis of factors influencing digital transformation of the time-honored enterprises:evidence from China - Jinhua He; Bingbing Xue; Fan Chen (Management System Engineering)
Abstract The digital transformation of time-honored enterprises is influenced by multiple factors, and research on their configurational effects holds significant importance for these enterprises to adapt to the digital transformation landscape. Based on the TOE theoretical framework, this study examines 40 Chinese time-honored enterprises and employs the fsQCA method to explore the diverse pathways for their digital transformation. The findings reveal: ①No single factor alone constitutes a necessary condition for the digital transformation of time-honored enterprises; instead, it is jointly influenced by multiple conditional variables, including technology management, investment in digital technology, digital attention allocation, corporate financial security, traditional cultural, and regional digitization. ②The configurational pathways for digital transformation in time-honored enterprises can be categorized into four types: The Attention-Financial Dual-Driven Model, The Management-Attention Synergy Type, The Investment-Culture Dual-Core Driven Type, and The Region-Technology Synergy Type. This research expands the theoretical scope of the TOE framework and provides a scientific decision-making basis for the digital transformation of time-honored enterprises.